2013
DOI: 10.1128/jcm.03108-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple-Locus Variable-Number Tandem-Repeat Analysis with Pulsed-Field Gel Electrophoresis Typing of Acinetobacter baumannii in China

Abstract: A panel of seven variable-number tandem-repeat (VNTR) markers was selected for Acinetobacter baumannii typing analysis (MLVA-7). Compared with pulsed-field gel electrophoresis (PFGE), MLVA-7 provided greater discrimination. We modified the criteria for MLVA complex assignments proposed previously, and a remarkable congruence between MLVA-7-and PFGE-based strain clustering was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…Amplification products were obtained for all VNTR markers except for Abaum_0845 in EE14 and EE15. A previously described, non-conserved 77–80 bp repeat unit in the Abaum_1988 locus [ 11 ] was detected in all PFGE types, instead of the 26 bp repeat unit described by Pourcel [ 10 ].…”
Section: Resultsmentioning
confidence: 93%
“…Amplification products were obtained for all VNTR markers except for Abaum_0845 in EE14 and EE15. A previously described, non-conserved 77–80 bp repeat unit in the Abaum_1988 locus [ 11 ] was detected in all PFGE types, instead of the 26 bp repeat unit described by Pourcel [ 10 ].…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, among L-loci, Abaum1998 yielded an ambiguous amplification pattern with two bands in 10 isolates. In a study by Hu et al, two different repeat units were obtained for locus Abaum1998 in all the tested isolates; thus, this locus was excluded from their MLVA scheme (23). However, in this study, an uncommon pattern was defined by "a" for 10 isolates and analyzed as an individual pattern.…”
Section: Discussionmentioning
confidence: 94%
“…MLVA has been developed for typing of various microbial species including Escherichia coli O157, Salmonella enterica, Pseudomonas aeruginosa, and A. baumannii (21)(22)(23). In the current study, MLVA-8 Orsay scheme was performed in order to trace the epidemiology of the carbapenem-resistant A. baumannii isolates and for bacterial differentiation at the strain level.…”
Section: Discussionmentioning
confidence: 99%
“…According to the report from Moradi et al, the prevalence of MDR isolates between 2008 and 2016 was ranged from 32.7% to 93% (18). The isolation of MDR A. baumannii in the ICU is more common and several outbreaks have been reported from Asian and European countries (8,(18)(19)(20)(21). Antibiotic susceptibility testing in this study showed that 21.8% of patients were infected by resistant strains to all tested antibiotics.…”
Section: Discussionmentioning
confidence: 95%